2017
DOI: 10.4038/jas.v12i2.8225
|View full text |Cite
|
Sign up to set email alerts
|

Elements of Rural Economics: Access to Agricultural Information among Rural Women Farmers in Abuja, Nigeria

Abstract: Information is very important for sustainable agricultural development. In order to increase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…There are many aspects to consider when focusing on the inequality of access to agricultural knowledge. A number of studies (Lawal, Alabi, and Oladele 2017;Mtega, Ngoepe, and Dube 2016;Rehman et al 2013) suggest that age has a significant influence on access to agricultural information. They found that adult male farmers (over 35 years of age, as defined by UNESCO (2017)) access more information than younger male farmers (under 35) do.…”
Section: Introductionmentioning
confidence: 99%
“…There are many aspects to consider when focusing on the inequality of access to agricultural knowledge. A number of studies (Lawal, Alabi, and Oladele 2017;Mtega, Ngoepe, and Dube 2016;Rehman et al 2013) suggest that age has a significant influence on access to agricultural information. They found that adult male farmers (over 35 years of age, as defined by UNESCO (2017)) access more information than younger male farmers (under 35) do.…”
Section: Introductionmentioning
confidence: 99%
“…Women also had problem of access to agricultural information, when adequate information are available to women farmers, experiences can be shared, sources of financial aids, best practices, and new markets will be made known to women. In order to improve agricultural production and attained agricultural sustainable development, information on agriculture is crucial for any nation (Lawal et al, 2017). Women productive capacity in the agricultural sector remains lower than their male counterparts, and thereby impacting adversely on overall productivity (Olakojo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The social effect has proven to make the agricultural sector more competitive (Hudeckova & Lostak, 2003). Many social factors, like advice from reference groups (pioneer farmers and family members), involvement in associations, culture, religion, and information technology can influence farmers' decisions (Noel, 2009;Kaewwongwattana et al, 2015;Lawal et al, 2017;Ataei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%